Hypertension in older adults: Assessment, management, and challenges - Oliveros, Estefania; Patel, Hena; Kyung, Stella; Fugar, Setri; Goldberg, Alan; Madan, Nidhi; Williams, Kim A. (Clinical cardiology (Mahwah, N.J.), 2020)
Hypertension in older adults is related to adverse cardiovascular outcomes, such as heart failure, stroke, myocardial infarction, and death. The global burden of hypertension is increasing due to an aging population and increasing prevalence of obesity, and is estimated to affect one third of the world's population by 2025. Adverse outcomes in older adults are compounded by mechanical hemodynamic changes, arterial stiffness, neurohormonal and autonomic dysregulation, and declining renal function. This review highlights the current evidence and summarizes recent guidelines on hypertension, pertaining to older adults. Management strategies for hypertension in older adults must consider the degree of frailty, increasingly complex medical comorbidities, and psycho‐social factors, and must therefore be individualized. Non‐pharmacological lifestyle interventions should be encouraged to mitigate the risk of developing hypertension, and as an adjunctive therapy to reduce the need for medications. Pharmacological therapy with diuretics, renin‐angiotensin system blockers, and calcium channel blockers have all shown benefit on cardiovascular outcomes in older patients. Given the economic and public health burden of hypertension in the United States and globally, it is critical to address lifestyle modifications in younger generations to prevent hypertension with age.